Yoga Education in Schools and Teacher Education Some Initiatives - Yadav, Saroj (JOURNAL OF INDIAN EDUCATION, 2016)
The word “Yoga” is derived from the Sanskrit word “yuj” which means “join” or “unite”. As an end, yoga signifies “integration of personality” at the highest level. Yoga is an ancient science and art of maintaining health and harmony of body and mind. It has been rediscovered having a potential role for developing physical, mental, emotional and social health of the children. Yoga has been highlighted even in the National Policy on Education, 1986. However, due importance was not given to yoga in the school curriculum. For the first time, adequate emphasis has been given to yoga in the National Curriculum Framework (NCF) 2005, by adding yoga to the curriculum and emphasising that the time allocated for games and yoga must not be reduced or taken away under any circumstances. In this paper, an attempt has been made to present the theoretical aspect of yogic practices, policy initiatives related to yoga in school education in terms of curriculum framework, development of syllabi and textual material. Initiatives taken at the teacher education level have also been reflected.